Strategi Coping Nelayan Terhadap Perubahan Iklim Studi, Pada Masyarakat Nelayan di Kecamatan Tugu, Kota Semarang Jawa Tengah - Alfi, Lailiyah; Juhadi, Juhadi; Heri, Tjahjono (Geo-Image, 2018)
The purpose of this research is, 1) knowing the phenomenon of climate change that affect the activities of fishermen in Tugu Sub-district, Semarang City. 2) identification the impact of climate change on fishermen community in Tugu Kota Semarang and 3) knowing coping strategy conducted by fisherman to climate change that happened in Tugu Sub-district Semarang City. The sampling technique in this research is simple random sampling. Data collection techniques used were observations, questionnaires, interviews, and documentation. Technique to data analysis used is descriptive analysis. The results showed that climate change in the coastal city of Semarang increasingly long. These changes include changes in wind speed, wave height, and rainfall. The impact felt by the fishermen is the change in the pattern of sea fishing , the cost of sea fishing increased 0 , 5 % and the change in catch decreased 10% . In addition, the three urban villages researched have the same coping strategy , which includes 4 aspects of coping strategy structural , economic, social and cultural.